Plasma phosphorylated tau181 as a biomarker of mild traumatic brain injury: findings from THINC and NCAA-DoD CARE Consortium prospective cohorts - Devoto, Christina; Vorn, Rany; Mithani, Sara; Meier, Timothy B.; Lai, Chen; Broglio, Steven P.; McAllister, Thomas; Giza, Christopher C.; Huber, Daniel; Harezlak, Jaroslaw; Cameron, Kenneth L.; McGinty, Gerald; et al. (Frontiers in Neurology, 2023)
Objective: To investigate phosphorylated tau (p-tau181) protein in plasma in a cohort of mild traumatic brain injury (mTBI) patients and a cohort concussed athletes.: This pilot study comprised two independent cohorts. The first cohort-part of a Traumatic Head Injury Neuroimaging Classification (THINC) study-with a mean age of 46 years was comprised of uninjured controls (UIC, n=30) and mTBI patients (n = 288) recruited from the emergency department with clinical computed tomography (CT) and research magnetic resonance imaging (MRI) findings. The second cohort with a mean age of 19 years, comprised 133 collegiate athletes with (n = 112) and without (n = 21) concussion. The participants enrolled in the second cohort were a part of a multicenter, prospective, case-control study conducted by the NCAA-DoD Concussion Assessment, Research and Education (CARE) Consortium at six CARE Advanced Research Core (ARC) sites between 2015 and 2019. Blood was collected within 48 hours of injury for both cohorts. Plasma concentration (pg/mL) of p-tau181 was measured using SIMOA ultrasensitive assay.